Effect of external basalt layers on durability behaviour of flax reinforced composites. (January 2016) - Fiore, V.; Scalici, T.; Calabrese, L.; Valenza, A.; Proverbio, E.
Abstract: Aim of this work is to evaluate the influence of external layers of basalt-mat on the durability behaviour of flax reinforced epoxy composites. To this scope, long-term ageing tests were performed on two different laminates in critical environmental conditions. The first laminate, named Flax, was constituted by stacking ten layers of bidirectional flax fabrics. The second one, named Flax–Basalt, was produced by replacing two external flax layers with two layers of basalt mat for each side of the laminate. Both laminates were exposed to salt-fog environmental conditions, according to ASTMB 117 standard, for 60 days. Five samples per laminate were removed from salt-fog spray chamber and mechanically tested. In particular, quasi-static flexural tests and Charpy impact tests were performed according to ASTMD 790 and ISO 179 standards, respectively. The fracture surfaces of both laminates were evaluated by using an optical 3D microscope. Moreover, five samples per laminate were removed periodically and weighed to evaluate the water absorption. The experimental results showed that the hybridization with basalt fibres can be considered as a practical approach for enhancing the durability of natural fibre composites under salt-fog environment conditions.